A Conceptual Model of the Effects of Taxation, Exchange Rate, and Regulations on the Transfer Pricing Behavior of Multinational Firm Managers - Alino, Nelson U.; Lane, Scott (Journal of Comparative International Management, 2016)
We review a sample of transfer pricing literature and conceptualize a moderated mediation model of the transfer pricing behavior of managers of multinational firms (MNFs). Our conceptual model suggests that transfer pricing decisions present complex problems to MNF managers that involve interactions between many factors, which could have many consequences, some of which may be at odds with each other. We provide relevant information to managers of MNFs and the regulatory agencies that will assist them in continuing the search for a regulatory and compliance frame work that works in the mutual interest of all relevant stakeholders.